Analysis of Heavy Metals in Soils around a Scrap Metal Recycling Company in Ile-Ife, Osun State, Southwestern Nigeria - O. Orisadare; H. Efunwole; M. Raimi (Fountain Journal of Natural and Applied Sciences (FUJNAS), 2020)
Contamination of soils by heavy metals has severely increased over the last few decades due to industrial wastes and human activities. Contaminated soils can constitute sources of health hazard to humans globally. However, there is paucity of information on the level of heavy metal concentration in the study area. This study therefore made a pioneering effort in investigating the concentration of selected heavy metals (Cd, Cu, Pb, Zn and Fe) in soils around a scrap metal recycling company in Ile-Ife, Osun State, Nigeria. Thirty soil samples and solid wastes were collected from four sides of the scrap metal recycling company. The samples were air-dried, digested using standard method and analyzed for the selected heavy metals using a flame atomic absorption spectrometer. Results of the Atomic Absorption Spectrophotometric (AAS) analysis revealed that for heavy metals, the concentrations in the soils were below the background levels and permissible limits recommended for soils in some countries. The value of the mean concentration of the analyzed heavy metals in the soils around the scrap metal recycling company ranged from 0.0040 – 0.0140 mg/kg for Cd, 0.061 – 0.108 mg/kg for Fe, 0.037 – 0.047 mg/kg for Cu, 0.003 – 0.0064 mg/kg for Pb and 0.019 – 0.121 mg/kg for Zn. The results from the study indicated that the concentrations of heavy metals around the scrap metal recycling company did not appear to be of serious concern. The concentrations of all the heavy metals were below the background level proposed by the World Health Organization (WHO) residential soil standards.